2021
DOI: 10.1186/s13019-021-01408-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the misdiagnosis of 8 adult cases of paragonimiasis with lung masses as the main manifestation in Xishuangbanna, Yunnan

Abstract: Objective To summarize the clinical characteristics of adult cases of paragonimiasis with lung masses as the main manifestation in Xishuangbanna, Yunnan Province, analyze the causes of misdiagnosis, and improve the levels of clinical diagnosis and treatment. Method We conducted a retrospective analysis of the clinical data and diagnosis and treatment of 8 adult cases of paragonimiasis with lung masses as the main manifestation that were diagnosed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For instance, in areas where tuberculosis and paragonimiasis overlap and patients are treated with antibiotics for long periods, the efficacy of the treatment of paragonimiasis may be impaired [46] . Rifampicin, for example, induces degrading enzymes and thereby reduces the plasma level of praziquantel to zero [8] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in areas where tuberculosis and paragonimiasis overlap and patients are treated with antibiotics for long periods, the efficacy of the treatment of paragonimiasis may be impaired [46] . Rifampicin, for example, induces degrading enzymes and thereby reduces the plasma level of praziquantel to zero [8] .…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case eggs are released into bronchioles, coughed up, mixed with sputum, and are either expectorated or swallowed for later excretion via feces. The clinical picture (cough, hemophthysis, fever, asthenia, pleura effusions, pulmonary masses, lung cavernae) is very similar to tuberculosis (TB) [8] . Therefore, paragonimiasis in Vietnam is also called "eosinophilic TB" (Richter 2002, personal observation, unpublished).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature on the identification of Paragonimus species among individuals consuming freshwater crabs is scarce. A recent study reported that 8 adult humans were infected with P. heterotremus, which were recovered from their lung masses on examination in Xishuangbanna, Yunnan [28]. In such a case, phylogenetic analysis is helpful in the identification of various species of organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al reported [14] that they observed clinical cases of pleuropulmonary paragonimiasis masquerading as pleural tuberculosis. Moreover, Shu et al [15] found that eight pleuropulmonary paragonimiasis patients experienced delayed diagnosis due to symptoms shared with lung masses, six were misdiagnosed as having pneumonia, and two were misdiagnosed as having pulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%